Use of high density SNP genotypes to determine the breed composition of cross bred dairy cattle in smallholder farms: Assessment of reproductive and health performance - Mujibi, F.D.N.; Ojango, Julie M.K.; Rao, E.J.O.; Karanja, T.; Kihara, Absolomon; Marete, A.; Baltenweck, Isabelle; Poole, Elizabeth J.; Rege, J.E.O.; Gondro, C.; Weerasinghe, W.M.S.P.; Gibson, John P.; et al. (American Society of Animal Science, 2014)
Reproductive performance and disease data were recorded for 2 years on 1,824 dairy cows in smallholder farms using participatory approaches and onfarm recording. Most animals experienced one service to conception. Calving intervals were long, ranging between 261 and 761 days, with an average of 451±101days. Herd level of production (HeL) had significant effect on calving interval. However, there was no difference between crossbreds with different levels of exotic breed percentage or in different HeL classes in disease incidence. Most animals had less than 2 treatment events, despite the high disease burden in the study areas. Mortality rates were low, ranging from 2.13% to 2.65%. Even though the crossbred animals had higher performance compared to indigenous animals, the gains obtained were below what would be possible with better management. These results suggest that crosses with low exotic proportions would be the most optimal for the production systems studied.